Participación de la vitamina D en la patogénesis de la infección por el virus de la inmunodeficiencia humana tipo 1 (2023)
Beyond its role in mineral metabolism, vitamin D (VitD) has immunomodulatory functions and can actively participate in the physiopathogenesis of HIV-1 infection; however, scientific evidence in this field is limited and controversial. VitD has anti-inflammatory properties that can reduce immune hyperactivation, decreasing the damage associated with this phenomenon. It also promotes the expression of antimicrobial peptides with anti-HIV-1 activity, supporting its protective role. In contrast, VitD activates the HIV-1 promoter and can increase viral replication. Furthermore, a number of allelic variants in the vitamin D receptor gene,which increase its function, have been associated with susceptibility to HIV-1 infection. Given the implications of this topic for the identification of new therapeutic targets in HIV infection, this review presents scientific evidence on the effect of the VitD pathway in HIV-1 pathogenesis. © 2013 ACIN.